Comparative Praxeology: Assessing High-Level Cognitive Skills in TIMSS and Indonesian National Examinations - Kania, Nia; Suryadi, Didi; Kusumah, Yaya S.; Dahlan, Jarnawi Afgani; Nurlaelah, Elah; Elsayed, Ebrahim E. (International Journal of Applied Learning and Research in Algebra, 2024)
Indonesian students perform inadequately in the International Mathematics and Science Study (TIMSS). Before utilising National Examination (UN) questions as measures of learning accomplishment, evaluating them within the context of a theoretical framework for mathematics education is imperative. They analyse student mathematical proficiency using TIMSS and National Examination questions and apply pedagogic anthropological theory, particularly praxeology. This study employed content analysis as a qualitative research method. An algebraic analysis was conducted using the praxeological technique. This entails evaluating concerns, approaches, and technological and theoretical alternatives (logo block). The results indicate that the TIMSS questions require careful consideration and analytical thinking. In contrast, National Examination questions restrict students' cognitive capacities to acquire knowledge on specific topics. The placement of national test question types will be determined based on analytical data. Indonesian students must enhance their arithmetic scores, which consistently remain low. To promote the growth of a highly skilled labour market, the government must comprehend the intricacies involved. Teachers should customise their classes to align with the individual learning objectives of each student.